Neem controls grasshoppers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Subsistence farmers in the Sahel could protect their crops against grasshoppers by making sprays from locally-grown neem trees. Sprays made from ground neem seeds are effective in reducing the amount of damage done to cereal crops by grasshoppers....